Gastric Perforation due to Fish Bone - Proença, AL (2020)
Unintentional ingestion of fish bones is a common but frequently unrecognized occurrence at the emergency room. Most ingested fish bones pass through the gastrointestinal tract without complications, but approximately 1% may perforate and cause acute abdomen, peritonitis and/or abscesses, requiring emergent surgery. Clinical presentation is non-specific and computed tomography is essential to confirm the diagnosis and guide the surgery. We present a case of gastric perforation by fish bone and discuss the clinical and radiological challenges in the diagnosis of this condition.